Development of recombinant subunit vaccines against Flavobacterium covae and Flavobacterium columnare in grass carp (Ctenopharyngodon idellus): Evaluation of protective efficacy and antibody immune response - Zhongning He; Rui Han; Huicheng Wu; Xueming Dan; Yanwei Li; Zequan Mo (Aquaculture, 2027)

Selective depression of fluorapatite by malic acid: The role of soluble calcium complexation in flotation separation from dolomite - Yuan Tang; Jinyang Guo; Fangyuan Li; Dongsheng He; Xueming Yin; Yanhong Fu; Zhili Li; Jiayu Ma (Minerals Engineering, 2026)

Lead and other elements in the diet of children (aged 0–7 years) across 20 Chinese provinces at a home-level survey: seasonal variations of element levels and risks in food, urine, and feces in healthy individuals - Maoyuan He; Xiaoping Li; Yu Gao; Pengyuan Jin; Zebo Yang; Jiayi Li; Xuelian Kui; Tunyang Geng; Xueming Zheng; Xu Zhang; Xiangyang Yan (Environmental Monitoring and Assessment, 2026)

Improved prediction for AFB1 in naturally contaminated peanut oil by fusing fluorescence with visible and near-infrared absorption and scattering properties - Xueming He; Yuanji Xiao; Yongnan Lu; Xiaoyun Yang; Fang Zhang (Food Control, 2026)

Delayed emission and pathway shift as drivers of N2O reduction in biological nitrogen removal with aniline exposure - Yingxin Jin; Xianli Yang; Yanying He; Xiang Li; Yingrui Liu; Tingting Zhu; Yufen Wang; Xueming Chen; Bing-Jie Ni; Yiwen Liu (Journal of Environmental Management, 2026)

Engineering a gradient SnO2-Sb-Nd electrode via synergistic defect and co-doping for ultrafast tetracycline degradation with robust durability - Xuening Bai; Yu Yang; Zhongxin Yang; Qiwen Zhang; Jian Zhang; Xuzhong Zeng; Miao He; Yejin Wang; Wenjing Yang; Anqi Li; Xueming Li (Journal of Environmental Chemical Engineering, 2026)

Rapid quality detection in colored potatoes during alternating cold and ambient storage: Utilizing absorption and scattering properties - Yuanji Xiao; Jianyu Wang; Jie You; Fang Zhang; Xueming He (Food Research International, 2026)

PRR11 as a newly identified oncogenic driver in retinoblastoma - Yu He; Xueming Ju; Huan Li; Mingze Li; Dan Zhang; Jialing Xiao; Yixiao Wu; Pu Zhang; Zhenglin Yang; Bo Gong (Science China Life Sciences, 2026)

Effects of Water-Fertilizer-Tillage Management on NH₃ Volatilization and Nitrogen Deposition in a Typical South China Agricultural System - Xiaoming He; Lingling Bi; Tianyi Chen; Siqi Yang; Shujuan Zhang; Siyi Yang; Chaohui Chen; Xin Wu; Xingjian Yang; Xueming Lin; Yongtao Li; Zhen Zhang (Water, Air, & Soil Pollution, 2026)

Analysis of critical thresholds for environmental impacts of deep-sea mining plumes in polymetallic nodule areas - Xueming Wang; Xuebao He; Juan Yang; Jianxin Xia (Acta Oceanologica Sinica, 2026)

The potential of mixotrophic denitrification for N2O mitigation: Insights from the perspective of electron distribution - Qian Lu; Yingrui Liu; Min Yan; Yanying He; Tingting Zhu; Xueming Chen; Bing-Jie Ni; Yiwen Liu (Journal of Cleaner Production, 2026)

Rapid and non-invasive identification of the AFB1 contaminated peanut by data fusion of hyperspectral imaging and laser induced fluorescence - Yiwen Zhuang; Xiaoyun Yang; Xueming He; Peng Li; Yong Fang (Food Control, 2026)

Mechanisms and mitigation strategies of N2O emission in response to metal nanoparticles in wastewater treatment: a review - Xianli Yang; Yanying He; Yingrui Liu; Hanwei Wang; Peiyao Zhang; Tingting Zhu; Yufen Wang; Yingxin Zhao; Yindong Tong; Xueming Chen; Bing-Jie Ni; Yiwen Liu (Journal of Cleaner Production, 2025)

Human Health Impact from Nonferrous Metal Mining: Exposure Risk with Hair as Biomarkers and the Associated Influencing Factors - Xueming Zheng; Feng He; Xiaoping Li; He Shen; Danqian Shi; Qishang Zhou; Shuang Zhang; Tunyang Geng; Yueheng Jiang; Pengyuan Jin; Xuelian Kui; Huimin Liu; et al. (Exposure and Health, 2025)

Lead seasonality: Affect children’s blood lead levels and implication for lead exposure prevention - Jie Dong; Xiaoping Li; Yu Zhang; Xueming Zheng; Shuang Zhang; Qishang Zhou; Feng He; Danqian Shi; Yueheng Jiang; He Shen; Xu Zhang; Ge Ma; et al. (Journal of Hazardous Materials, 2025)

Recovery of AFB1 intrinsic fluorescence in vegetable oils with continuous variations in matrices by theoretical analysis and experiments - Meng Wang; Xiaoqi Zhao; Xiaoyun Yang; Xueming He (Food Chemistry, 2025)

Using machine learning to predict soil lead relative bioavailability - Shuang Zhang; Xiaoping Li; Tunyang Geng; Yu Zhang; Weixi Zhang; Xueming Zheng; He Sheng; Yueheng Jiang; Pengyuan Jin; Xuelian Kui; Huimin Liu; Ge Ma; et al. (Journal of Hazardous Materials, 2025)

Nondestructive and robust detection of different kinds of vegetable oils adulterated with used frying oil by multi-optical properties - Jie You; Xinyu Zhang; Xueming He (Food Research International, 2025)

New insights to chlorination-induced chemical bond cleavage in polyamide membranes: Degradation mechanisms and the role of calcium and magnesium ions - Qinyu Yu; Shuang Wu; Linyan Yang; Xueming Chen; Min Tao; Yi Wu; Xiaowei He; Lichun Bai; Shujuan Meng (Chemical Engineering Journal, 2025)

Research on urban thermal environment differentiation based on functional zones------take four districts of Dalian as an example - Xiaohui Zhang; Xueming Li; He Liu; Yishan Song; Mengke Gao (Urban Climate, 2024)

Lactococcus garvieae as a Novel Pathogen in Cultured Pufferfish (Takifugu obscurus) in China - Ruilong Xu; Zhongning He; Yiyang Deng; Yihao Cen; Zequan Mo; Xueming Dan; Yanwei Li (Fishes, 2024)
In October 2023, a disease outbreak in pufferfish (Takifugu obscurus) farms in Zhongshan City, Guangdong, China, caused high mortality. Diseased fish (mean length: 15 ± 1 cm) exhibited swimming disorders, fin rot, hemorrhage, and an enlarged spleen. Histopathological observations generally revealed inflammation, necrosis, and congestion in the spleen, kidneys, and brain tissues. The most severe pathological changes included interstitial edema and tubular atrophy in the kidneys, hemosiderin deposition in the spleen, massive red blood cell infiltration, and a decrease in lymphocytes. A single strain of bacteria (Tol-1) was isolated from the diseased pufferfish and identified as a Gram-positive streptococcus strain, exhibiting α-hemolysis on sheep blood agar plates. Through biochemical characterization, 16S rDNA sequencing, morphological analysis, and specific primer-based identification, the Tol-1 strain was identified as Lactococcus garvieae, serotype I. Antimicrobial susceptibility testing indicated that Tol-1 was sensitive to Chloramphenicol, Ampicillin, Cephalexin, and Doxycycline, but resistant to Kanamycin, Gentamicin and Ciprofloxacin. In addition, 15 common virulence factors were detected in the Tol-1 strain, including adhPav, adhPsaA, adhC I–II, adh, and hly 1–3. Pufferfish (mean length: 17 ± 1 cm) subjected to artificial infection via intraperitoneal injection (IP) with the Tol-1 strain exhibited clinical symptoms and histopathological damage similar to those observed in naturally infected fish. An infection dose of 1 × 105 CFU/fish resulted in 80% mortality. The study fulfilled Koch’s postulates, indicating that the disease outbreak in pufferfish was caused by L. garvieae, which exhibited a high mortality rate in pufferfish despite the subtle clinical symptoms. These results serve as a warning for pufferfish farming areas and provide a scientific basis for future prevention and control efforts.

Contribution of yeast freezing to the quality of frozen dough: Rheological properties, protein depolymerization, gluten conformation and water state - Lunan Guo; Xinyang He; Yihang Wang; Guodong Liu; Chunsen Wu; Xueming Xu; Jian-Ya Qian (Food Bioscience, 2024)

Constructing 3D sandwich-like structured Ti foam/TiO2−x/SnO2-Sb composite electrodes for the degradation of PPCPs - Anqi Li; Xuening Bai; Yuting Xie; Hebin Bao; Yu Yang; Miao He; Wenjing Yang; Qiwen Zhang; Yunhuai Zhang; Xueming Li (Chemical Engineering Journal, 2024)

A novel method for determination of peroxide value and acid value of extra-virgin olive oil based on fluorescence internal filtering effect correction - Xiaoyun Yang; Jingyu Pei; Xueming He; Yue Wang; Liu Wang; Fei Shen; Peng Li; Yong Fang (Food Chemistry, 2024)

Insight into the interaction mechanism between mulberry polyphenols and β-lactoglobulin - Qi Yuan; Lin He; Xuping Wang; Huaigu Yang; Fan Zhu; Xiaoxia Peng; Jingrong Cheng; Yaosheng Lin; Daobang Tang; Xueming Liu (Food Hydrocolloids, 2024)

Metabolomics reveals the phytotoxicity mechanisms of foliar spinach exposed to bulk and nano sizes of PbCO3 - Qishang Zhou; Xiaoping Li; Xueming Zheng; Xu Zhang; Yueheng Jiang; He Shen (Journal of Hazardous Materials, 2024)

Machine learning integrated high quantum yield blue light carbon dots for real-time and on-site detection of Cr(VI) in groundwater and drinking water - Mengyuan Zhang; Haijun He; Yanquan Huang; Renfeng Huang; Zhen Wu; Xueming Liu; Hong Deng (Science of The Total Environment, 2023)

Effect of modified atmosphere packaging assisted cold plasma on performance of edible soybean protein isolate films - Qi Li; Ai Zhi; Xueming He; Fei Shen; Yong Fang; Qiuhui Hu; Xingquan Liu (Food Bioscience, 2023)

Pilot test of high-pressure water jet slotting with liquid CO2 injection to displace CH4 and improve coal seam permeability - Wansheng Mi; Hu Wen; Shixing Fan; Gaoming Wei; Mingyang Liu; Shibin Wang; Haihong He; Xueming Wu; Xiaojiao Cheng; Bocong Liu; Rijun Li (Fuel, 2023)

High thermal conductivity of porous graphite/paraffin composite phase change material with 3D porous graphite foam - Xueming Yang; Chunbo Li; YongFu Ma; He Chi; Zongjie Hu; Jianfei Xie (Chemical Engineering Journal, 2023)

Preparation and characterization of PMT-TiO2-NTs@NiO–C/Sn–Sb composite electrodes by a two-step pulsed electrodeposition method for the degradation of crystalline violet - Anqi Li; Xuening Bai; Yuting Xie; Pengyang Xia; Hebin Bao; Miao He; Xuzhong Zeng; Wenjing Yang; Xueming Li (Chemosphere, 2023)

Aflatoxins degradation and quality evaluation in naturally contaminated rice by dielectric barrier discharge cold plasma - Ai Zhi; Shanshan Shi; Qi Li; Fei Shen; Xueming He; Yong Fang; Qiuhui Hu; Xuesong Jiang (Innovative Food Science & Emerging Technologies, 2023)

Evaluation of nitrogen removal and nitrous oxide turnovers in granule-based simultaneous nitrification and denitrification system - Feng Chen; Yingrui Liu; Yanying He; Xueming Chen; Tingting Zhu; Yiwen Liu (Science of The Total Environment, 2023)

Simultaneous detection of Aspergillus moulds and aflatoxin B1 contamination in rice by laser induced fluorescence spectroscopy - Bei Wang; Fei Shen; Xueming He; Yong Fang; Qiuhui Hu; Xingquan Liu (Food Control, 2023)

Modification of soy protein isolate using dielectric barrier discharge cold plasma assisted by modified atmosphere packaging - Qi Li; Fei Shen; Xueming He; Changrui Xing; Wenjing Yan; Yong Fang; Qiuhui Hu (Food Chemistry, 2023)

Mathematical modeling of the dynamic effect of denitrifying glycogen-accumulating organisms on nitrous oxide production during denitrifying phosphorus removal - Shuqi Ren; Yingrui Liu; Yanying He; Tingting Zhu; Xueming Chen; Yiwen Liu (Chemical Engineering Journal, 2023)

Underwater self-sustaining combustion and micro-propulsion properties of Al@FAS-17/PTFE-based direct-writing nanothermite - Haifeng Yang; Chuanhao Xu; Weimiao Wang; Pengfei Tang; Xiaodong Li; Shanshan He; Hebin Bao; Shuaishuai Man; Deyun Tang; Xueming Li; Guangcheng Yang; Zhiqiang Qiao (Chemical Engineering Journal, 2023)

Study on the heat transfer in different aquifer media with different groundwater velocities during thermal conductive heating - He Sun; Xueming Qin; Xinru Yang; Yongsheng Zhao (Environmental Science and Pollution Research, 2020)

Proton Oriented-“Smart Depot” for Responsive Release of Ca2+ to Inhibit Peptide Acylation in PLGA Microspheres - Jiwei Liu; Yan Xu; Yonglu Wang; Hao Ren; Zhengjie Meng; Kuntang Liu; Zhe Liu; He Huang; Xueming Li (Pharmaceutical Research, 2019)

Upregulation of HRD1 promotes cell migration and invasion in colon cancer - Xueming Tan; Xiaolu He; Zhining Fan (Molecular and Cellular Biochemistry, 2019)

Derlin-1 is overexpressed in human colon cancer and promotes cancer cell proliferation - Xueming Tan; Xiaolu He; Zhonghua Jiang; Xiaohong Wang; Limei Ma; Li Liu; Xiang Wang; Zhining Fan; Dongming Su (Molecular and Cellular Biochemistry, 2015)

Numerical study of ural blocking high’s effect upon Asian summer monsoon circulation and East China flood and drought - He Jinhai; Zhou Xueming; Ye Rongsheng (Advances in Atmospheric Sciences, 1995)